Scoping Review: Faktor Promotif Kinerja Organisasi - Sumarlin, Yanti Ariani; Sutisna, Deden (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This research aims to identify promotive factors of organizational performance using scoping review method. Based on analysis of 21 articles from ScienceDirect and Taylor & Francis Online databases, this research found that organizational performance is influenced by two main promotive factors, namely internal and external promotive factors. Internal promotive factors have a dominant contribution, with four main variables identified: (1) positive organizational culture, (2) positive leadership, (3) positive management system, and (4) positive employee attitudes and behavior. Positive organizational culture is the variable most often discussed, especially aspects of innovation, communication, learning culture, and recognition of employees. This research recommends further exploration of the contribution of external promotive factors as well as the interaction between internal and external promotive factors to provide a more comprehensive understanding of organizational performance. In addition, researchers also recommend intervention programs which are further discussed in this article.